RETIREMENT PLANNING FOR THE WORKER: A Financial Behavior Management Model Moderated By Social Influence - Etty Sri Wahyuni; Rozaini Binti Rosli (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
This study examines the complex dynamics of retirement planning among manufacturing workers in Batam, Indonesia, focusing on the interplay between financial behavior, social influence, and retirement planning outcomes. Utilizing a quantitative associative approach, the research surveyed 100 workers from diverse demographic backgrounds in Batam's manufacturing sector. The study employed Smart-PLS 3 software for structural equation modeling and path analysis. Key findings reveal that while financial behavior positively influences retirement planning (β=0.196, p=0.032), social influence exhibits a much stronger positive effect (β=0.858, p=0.000). Interestingly, social influence negatively moderates the relationship between financial behavior and retirement planning (β=-0.176, p=0.037), suggesting that social factors may sometimes counteract individual financial practices. These results underscore the complexity of retirement planning in industrial urban settings, highlighting the need for a nuanced approach that considers both individual financial literacy and broader social contexts. The study concludes by recommending holistic strategies that combine traditional financial education with community-based interventions to enhance retirement planning effectiveness among workers in rapidly developing industrial cities like Batam.